1999
DOI: 10.1021/jo9910278
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Enantiomerically Pure Cyclopropanes from Cyclopropylboronic Acids

Abstract: A general method for the stereocontrolled synthesis of cyclopropanes is described. Various, highly stable, enantiomerically pure alkenylboronic esters 13 have been conveniently synthesized by the direct hydroboration of alkynes 11 using the new chiral 1,3,2-dioxaborolane 15. The high stability was also demonstrated by the selective deprotection of a tert-butyldimethylsilyl protecting group without hydrolyzing the boronic ester. The diastereoselective cyclopropanation of the olefins was achieved by the palladiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(60 citation statements)
references
References 44 publications
2
58
0
Order By: Relevance
“…247,252,253 During the coupling reaction, the absolute configuration of the cyclopropyl group was retained. Soderquist et al have reported the hydroxy(cyclopropyl)-9-BBN complex 239, which undergoes an efficient crosscoupling reaction under mild conditions to produce a variety of aryl-and vinylcyclopropanes in good to excellent yield (Scheme 109).…”
Section: Coupling Of Sp 3 Hybridised C -B Compoundsmentioning
confidence: 99%
“…247,252,253 During the coupling reaction, the absolute configuration of the cyclopropyl group was retained. Soderquist et al have reported the hydroxy(cyclopropyl)-9-BBN complex 239, which undergoes an efficient crosscoupling reaction under mild conditions to produce a variety of aryl-and vinylcyclopropanes in good to excellent yield (Scheme 109).…”
Section: Coupling Of Sp 3 Hybridised C -B Compoundsmentioning
confidence: 99%
“…[53] Then, using an enantiopure cyclopropylboronic acid in the presence of bromobenzene, iodobenzene or 1-bromonaphthalene, Pietruszka and Luithle were able to obtain enantiopure arylcyclopropanes. [54] They have also reported the coupling of a bicyclopropyl derivative with iodobenzene in good yield (Scheme 30). [55] Finally, in 2003 Pietruszka and co-workers reported the arylation of a functionalised cyclopropylboronic acid.…”
Section: Alkylations Of Aryl Halides With Secondary Alkylboronic Acidmentioning
confidence: 99%
“…The cyclopropanation was most conveniently performed by using diazomethane in the presence of catalytic amounts of Pd(OAc) 2 . [64,65] The conversion is usually high, however, in order to obtain pure cyclopropylboronic esters 23, some loss during work-up was acceptable. Oxidation to cyclopropanols 24 and acetylation to 25 using standard conditions was unproblematic (Scheme 7), nevertheless, some loss of material during distillation was observed.…”
Section: Cyclopropanolsmentioning
confidence: 99%
“…[59±63] (known compounds: 22b, [65] 22h, [77] and 22i [63] ), cyclopropylboronic esters 23 (known compounds: 23b [65] and 23h [77] ), cyclopropanols 24 (known compounds 24a [70] and 24c [69] ), and vinyl acetate 26.…”
Section: Experimental Section General Remarksmentioning
confidence: 99%